(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
This article describes the theoretical and methodological foundations of the development of students’ axiological attitude to historical and spiritual ideals. The article also describes the differences and similarities between historical ideals and cultural ideals. The theoretical and practical situation of the problem of developing axiological attitude of students to historical and spiritual ideals is described in this article.